Optimizing Agile Project Management In Fintech: A Literature Review On Evaluating The Efficacy Of Scrum Using Discrete Event Simulation. - AlBabtain, Hala (Journal of Namibian Studies, 2024)
Agile methodologies have become integral to modern tech, offering flexibility, adaptability, and iterative development processes that are particularly beneficial in dynamic and fast-paced industries. This literature review examines the evolution of Agile Project Management, comparing Agile methodologies with traditional project management approaches to highlight their respective strengths and limitations. The Scrum framework, a popular Agile methodology, is explored in detail, focusing on its application in the fintech sector. Metrics for assessing the effectiveness, efficiency, and adaptability of project management methodologies are discussed, emphasizing the importance of continuous improvement. Then, the review introduces Discrete Event Simulation (DES) as a tool for assessing and optimizing Scrum practices. DES's ability to model complex systems and simulate various scenarios provides a quantitative approach to evaluating and enhancing project management frameworks. Key findings indicate that DES can significantly improve workflow efficiency, team dynamics, and project outcomes in Scrum environments. The implications for fintech companies are substantial, suggesting that integrating Agile methodologies with DES can drive innovation, enhance project management efficiency, and maintain competitive advantage in the rapidly evolving financial services landscape.